Russian Church Abroad and the beginning of the “Free Church” (1990–1995) - Andrey Kostryukov (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi)
The article is devoted to the history of the creation of a non–canonical structure by the Russian Church Abroad - the so-called "Russian Orthodox Free Church" (ROSC). The article explores the reasons why the ROCOR in 1990, instead of reconciliation with the Moscow Patriarchate, went to confrontation, creating dioceses on its canonical territory. The reasons why the Russian Orthodox Church did not become popular in the Orthodox environment and was marginalized at the very beginning of the 1990s are also being investigated. The reasons for the conflict between this structure and the ROCOR leadership are also considered. Based on documents and materials, as well as the periodicals of the ROCOR and the Russian Orthodox Church, it is concluded that the reason for the failure of the "Free Church" was, first of all, the misunderstanding of the leadership of the Church Abroad of Russian realities, groundless confidence that the Russian population will massively move to a new structure. Among other reasons is the impoverishment of the spiritual and intellectual forces of the ROCOR, confident in the success of the new project. The result was an unsuccessful personnel policy, the admission of far from the best representatives of the clergy to the Russian Orthodox Church. In parallel with the problems that began, representatives of the Russian Church Abroad began to understand that its "return" to its homeland should take place not through the creation of a non-canonical parallel "Church", but through dialogue